THE NOTION OF “FREEDOM OF SPEECH” ON THE PAGES OF THE KUBAN PRESS IN THE PERIOD OF THE FIRST RUSSIAN REVOLUTION (Proceedings of Southern Federal University. Philology, 2012)
Khokhlach J.L.Keywords: the first Russian revolution, «Kubanskie oblastnye vedomosti», the newspaper «Kuban», «Zarya», freedom of speech, censorship.The article is devoted to a qualitatively new stage in the development of domestic journalism, which it experienced in the period of the First Russian revolution (1905 - 1907). At this time prior censorship was cancelled, as well as the right of the Home Minister to prohibit the discussion in the press the issues of national importance. The article presents the analysis of the publications devoted to freedom in particular, in the official newspaper «Kubanskie oblastnye vedomosti» and progressive newspapers «Kuban» and «Zarya».